2014
DOI: 10.1016/j.foodhyd.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Self-structuring foods based on acid-sensitive low and high acyl mixed gellan systems to impact on satiety

Abstract: This study investigated the in vitro acid-induced gelation of mixed systems of two biopolymers; low acyl and high acyl gellan gum. Rheological and texture analysis showed that these mixed gels displayed textures that lay between the material properties exhibited for the low and high acyl variants. DSC analysis showed that mixtures of the low acyl and high acyl forms exhibit two separate conformational transitions at temperatures coincident with each of the individual biopolymers.Various metabolically relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 33 publications
4
17
0
1
Order By: Relevance
“…In the present work, increasing LAG content produced a firmer gel matrix that could hinder the partial breakup of the structure and decrease the overshoot height leading to a strain thinning behavior due to layers sliding past each other in the flow direction. This behavior is in agreement with several authors who reported an increase in gel brittleness with increasing the low acyl gellan content (Bradbeer, G. Lorenzo et al / Carbohydrate Polymers xxx (2014) xxx-xxx Hancocks, Spyropoulos, & Norton, 2014;Foo, Liong, & Easa, 2013;Kasapis et al, 1999;Sworn, 2000).…”
Section: Rheological Properties: Large Amplitude Oscillatory Shearsupporting
confidence: 92%
“…In the present work, increasing LAG content produced a firmer gel matrix that could hinder the partial breakup of the structure and decrease the overshoot height leading to a strain thinning behavior due to layers sliding past each other in the flow direction. This behavior is in agreement with several authors who reported an increase in gel brittleness with increasing the low acyl gellan content (Bradbeer, G. Lorenzo et al / Carbohydrate Polymers xxx (2014) xxx-xxx Hancocks, Spyropoulos, & Norton, 2014;Foo, Liong, & Easa, 2013;Kasapis et al, 1999;Sworn, 2000).…”
Section: Rheological Properties: Large Amplitude Oscillatory Shearsupporting
confidence: 92%
“…An alternative would be to incorporate another biopolymer that is multicomponent system, such that the mixture may possess properties which cannot be achieved in the case of the single biopolymer system. This can be done by manipulating the phase behaviour of a mixture whereby the continuous phase is of lower viscosity (Goh et al ., ), or via self‐assembly of the biopolymers postingestion in an acidic digestive environment (Hoad et al ., ; Rayment et al ., ; Bradbeer et al ., ; Zhang & Vardhanabhuti, ). For food systems with the same composition, the nutrient release, bioavailability and digestive mechanism are governed by the microstructure of the food matrix to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…The force/distance (of compression) data, as obtained directly from the texture analyser, was converted into true strain (Ɛ H ) and true stress (s T ) data to obtain true stress/true strain curves for all of the LA gellan gum fluid and acid fluid gel acid structures according to Bradbeer, Hancocks, Spyropoulos, and Norton (2014). From the obtained true stress/true strain curves, the slope of the initial linear region (up to strain values of 0.05%) can be used to calculate the Young's modulus (Smidsrød, Haug, & Lian, 1972) while the slope of the second linear region (for strain values over~0.1%), leading to the subsequent structure failure can be used to calculate the bulk modulus (Nussinovitch, 2004).…”
Section: Texture Analysismentioning
confidence: 99%
“…It is widely accepted (Norton, Cox, & Spyropoulos, 2011;Yamamoto & Cunha, 2007) that LA gellan is acid-sensitive. Research (Bradbeer et al, 2014;Norton et al, 2011) has shown that LA gellan gum gel strength increases on exposure to an HCl acid soak. This is a result of the existing gel networks already partially formed within the gels prior to soaking being reinforced on acid exposure.…”
Section: Texture Analysis and Post-production Exposure To Acidic Envimentioning
confidence: 99%